Komunikasi Simbolik Dalam Tradisi Mandi Kasai Di Kelurahan Batu Urip Taba Kota Lubuklinggau - Maharani, Rara Aziza; Apriani, Lusi; Abisyiwih, Firman; Sumarni, Retno (STAI Bumi Silampari, 2024)
This research discusses the role of traditional leaders in maintaining the Kasai bathing tradition, where the Kasai bathing tradition is one of the traditions of the city of Lubuklinggau, South Sumatra province. Here the researcher describes the implementation of the traditional kasai bathing culture and the meaning contained in the traditional kasai bathing tradition in the city of Lubuklinggau. Then examine the perceptions of traditional leaders in maintaining the Kasai bathing tradition in the city of Lubuklinggau. The results of this research show that the traditional kasai bathing ceremony is part of the traditional marriage ceremony in the people of Lubuklinggau City. This ceremony is carried out by the bride and groom after giving alms with the facilities and infrastructure for the ceremony. The traditional kasai bathing ceremony has two meanings: (a) the bride and groom release their teenage years in the sense of freedom to mingle among bujang-dere (young people); (b) before entering married life, the bride and groom must be clean and pure. The perception of the people of Lubuklinggau City regarding the traditional kasai bathing ceremony tradition is different, some are supportive and some are less supportive, in this case the role of traditional leaders and the community is needed to continue to preserve the kasai bathing culture so that this culture is not lost.